Efektivitas Sport Education Model Terhadap Pengetahuan Teori Permainan Bola Voli - Komarudin Agung Suhara; Febriyanti Cahyaningtias; Harvenes Chandra; Imam Abdul Aziz; Maulana Syarif; Ega Trisna Rahayu (JURNAL PENA EDUKASI, 2022)
Abstract : Education is an effort or government program in educating the nation, so it becomes an important and mandatory thing to do because education has a fundamental nature concerning the quality of human resources as the basis for development. physical education is one of the processes in education to achieve a goal with physical movement by doing it consciously and systematically through several activities in the body. physical education learning there are several domains, namely the psychomotor domain (movement), the cognitive domain (knowledge) and the affective domain (values or behavioral attitudes).Volleyball learning is one type of physical education. volleyball itself is a big ball game played in 2 groups each group consisting of 6 players for the field.The Sport Education Model is to encourage students to play a variety of roles from sports, namely as players, in sport education, students learn to become coaches, referees, and scorekeepers. The goal achieved in this study is to see how far the knowledge of class X students at SMK Panca Moral Cikampek about volleyball..Keywords: education, volleyball, sport education model Abstrak:Pendidikan adalah satu upaya atau program pemerintah dalam mencerdaskan bangsa, sehingga menjadi suatu hal yang penting dan wajib dilakukan karena pendidikan mempunyai sifat yang mendasar menyangkut kualitas sumber daya manusia sebagai dasar dalam pembangunan..Pendidikan jasmani adalah salah satu proses dalam pendidikan untuk mencapai suatu tujuan dengan gerak fisik dengan melakukannya  dengan sadar dan sistematik melalui beberapa kegiatan dalam jasmani.pembelajaran pendidikan jasmani terdapat beberapa domain, yaitu domain psikomotor(gerak),domain kognitif(pengetahuan) dan domain afektif(nilai atau sikap perilaku).Pembelajaran bola voli adalah salah satu jenis ada pada Pendidikan jasmani. volleyball sendiri yaitu permainan bola besar yang dimainkan dalam 2 grup setiap grupnya terdiri dari 6 pemain untuk di lapangan.Sport Education Model yaitu mendorong siswa memainkan berbagai macam peran dari olahraga yaitu sebagai pemain,Didalam sport education, peserta didik belajar menjadi pelatih, wasit, dan pencatat score. Tujuan yang dicapai dipenelitian ini yaitu untuk meliht seberapa jauh pengetahuan siswa kelas X  di SMK Panca Moral Cikampek tentang bola voli. Kata Kunci: Pendidikan, Bola Voli, Sport Education Model.